CdSe quantum dots capped PAMAM dendrimer nanocomposites for sensing nitroaromatic compounds - algarra, m (2011)
The detection of nitroaromatic compounds, best known as raw materials in explosives preparations, is important in many fields including environmental science, public security and forensics. CdSe quantum dots capped with PAMAM-G(4) dendrimer were synthetized in water and used for the detection of trace amounts of three nitroaromatic compounds: 4-methoxy-2-nitrophenol (MNP), 2-amine-5chloro-1,3-dinitrobenzene (ACNB) and 3-methoxy-4-nitrobenzoic acid (MNB). To increase the apparent water solubility of these compounds alpha-cyclodextrin (alpha-CD) was used to promote the formation of inclusion complexes. The studied nitroaromatic compounds (plus alpha-CD) significantly quenched the fluorescence intensity of the nanocomposite with linear Stern-Volmer plots. The Stern-Volmer constants (standard deviation in parenthesis) were: MNB, K(SV) = 65(5) x 10(4) M(-1); ACNB, K(SV) = 19(2) x 10(4) M(-1); and, MNP, K(SV) =33(1) x 10(2) M(-1). These constants suggest the formation of a ground state complex between the nitroaromatric compounds and the sensor which confers a relatively high analytical sensitivity. The detection sensibilities are about 0.01 mg L(-1) for MNB and ACNB and about 0.1 mg L(-1) for MNP. No interferences or small interferences are observed for trinitrotoluene [K(SV) =10(2) x 10(2) x M(-1)], 2,4-dinitrotoluene [K(SV) = 20(3) x 10 M(-1)], 2,6-dinitrotoluene [K(SV) = 11(4) x 10 M(-1)] and nitrobenzene [K(SV) = 2(1) x 10(3) x M(-1)].